Double gas treatment: A successful approach for stabilizing the Li and Mn-rich NCM cathode materials’ electrochemical behavior - Maiti S.; Sclar H.; Rosy; Grinblat J.; Talianker M.; Tkachev M.; Tsubery M.; Wu X.; Noked M.; Markovsky B.; Aurbach D. (My University, 2025)
Herein, a systematic surface modification approach via double gas (SO2 and NH3) treatment at elevated temperatures is described, aimed to achieve a stable electrochemical performance of Li and Mn-rich NCM cathode materials of a typical composition 0.33Li2MnO3·0.67LiNi0.4Co0.2Mn0.4O2 (HE-NCM). Partial surface reduction of Mn4+ and the formation of a modified interface comprising Li-ions conductive nano-sized Li2SO4/Li2SO3 phases are established. Li-coin cells’ prolonged cycling performance demonstrated significantly improved capacity retention (∼2.2 times higher than untreated cathode materials) for the double-gas-treated cathodes after 400 cycles at a 1.0 C rate. Stable discharge potential and lower voltage hysteresis during cycling were also achieved through the double gas treatment. Comparative electrochemical studies in full-pouch cells [vs. Graphite anodes] also demonstrated considerably stabilized electrochemical behavior for the double-gas-treated HE-NCM cathode materials. Lower gasses (O2, CO2, and H2) evolution in the first charge-discharge cycle and improved thermal stability are indeed crucial achievements of this treatment. Electrodes’ post-cycling investigation revealed morphological integrity of the gas-treated cathode materials and lower transition metals (TMs) dissolution from the active cathodes. The positive effects of the double gas treatment are clearly related to the modified surfaces and lessening undesirable side reactions at the electrode-electrolyte solution interface. © 2021 Elsevier B.V.